CLIL intervention proposal to improve students’ oral communication in the natural science area at 5th year, through the use of cooperative learning and scaffolding - Campillo-Fuentes, Carmen (My University, 2016)
Nowadays, English language has become a basic and essential tool to function in an increasingly globalized society. In this context, the CLIL approach appears as an appropriate methodology to ensure that children and young people reach an adequate language level. In this work we have designed an intervention proposal in the Natural Science area to help students at 5th year to improve their oral communication through the CLIL approach. We provide students with opportunities to develop their oral communication as one of the main objectives of the Primary Education is that students have to acquire communicative competence in at least one foreign language. The work also includes a theoretical study on the CLIL methodology in which this proposal is based, where we address the principles and main characteristics of this approach. Later, we mainly focus on one of the features of this methodology which is scaffolding, considering the scaffolding key features, scaffolding strategies and different types of scaffolding, of which we highlight the peer-scaffolding. In the theoretical study we also refer to cooperative learning because language learning is done with social interaction and therefore throughout the design of our intervention proposal we have provided students to work cooperatively with different types of grouping and using different cooperative work strategies. The general aim of this Master’s Dissertations is to find out how the implementation of scaffolding and cooperative learning in a CLIL context can benefit the development of our Primary students’ oral communication. Finally, we consider very interesting the possibility of extending the intervention proposal we have designed to other skills like reading, writing or listening, to other topics, subjects and other levels as could be Pre-Primary Education, Primary Education and Secondary Education.
Keywords: CLIL; oral communication; foreign language (FL); scaffolding; cooperative learning (CL); primary education; enseñanza bilingüe; Máster Universitario en Educación Bilingüe